QUALITY CONTROL ANALYSIS ON WHITE CRYSTAL SUGAR PRODUCTS USING STATISTICAL PROCESSING CONTROL AND SEVENTOOLS METHODS AT PT. XYZ - Rahadian Trisna Kusuma Kusuma; Wiwik Sulistiyowati (Antis Publisher, 2025)
Objective: PT. XYZ is a manufacturing company that produces white crystalline sugar, which is a natural sweetener from sugarcane raw materials used as raw materials for households and the food industry. At PT. XYZ has a problem, namely the number of defects exceeds the standard in the company, namely in June amounted to 52,702 (Ku), July 64,282 (Ku), August 69,741 (Ku), while the number of defects in June amounted to 304.5 (Ku), July amounted to 357.5 (Ku), and August amounted to 39 (Ku) with a defect percentage in 3 months of 0.6%. Method: From these data, it shows that these conditions exceed the established standard (Zero Defect) and improvement must be carried out. The solution to this problem uses the methods of Statistical Processing Control and Seven Tools. Result: The results of the data calculation are the highest defects in refined sugar by 51%, gravel sugar by 40%, and sapon sugar by 9%, this is due to the production process not being maximized because of the lack of supervision by superiors during the production process. Novelty: This study provides an applied approach in identifying and analyzing production defects using Statistical Processing Control and Seven Tools to support quality improvement and minimize product defects, offering a practical contribution to continuous improvement in the sugar manufacturing industry.